PENERAPAN MODEL PEMBELAJARAN THINK TALK WRITE UNTUK MENINGKATKAN KETERAMPILAN MENULIS SISWA KELAS V SD NEGERI 158 PEKANBARU - Mimin Marta; Otang Kurniaman; Lazim N. Lazim N. (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research is motivated by the low skill of students in writing the summary. Out of 20 students are grouped into several categories. Very skilled 0 students (0%), skilled 2 students (10%), skilled enough 11 students (55%), and less skilled 7 students (35%). The purpose of this research is to describe the improvement of writing skills of fifth grader SDN 158 Pekanbaru through the think talk write model. Teacher activity has increased in each cycle. The first meeting of the cycle I percentage of teacher activity 69%, the second meeting in the first cycle increased to 72%, the first meeting in cycle II was 75% and increased to 88% in the second meeting of cycle II. Student activity at each meeting also increased. The first meeting of the cycle I percentage of student activity was 67%, the second meeting of cycle I increased to 69%, the first meeting of cycle II was 75% and increased to 94% in the second meeting of cycle II. The initial average score of the students before the applied think-writing write learning model was 55.75. After applying the think talk write model, in Deuteronomy Daily Cycle I experienced an average increase of 69.9 with an increase percentage of 25.38%. Then in Deuteronomy Daily Cycle II student's average skills increased to 79.25 with a percentage increase of 42.15%. From this research can be concluded that by applying the model of think talk write learning can improve writing skill of fifth grader elementary school state 158 Pekanbaru.Key Words: think talk write, writing skills